Visualizing eggs of Nesidiocoris tenuis (Heteroptera: Miridae) embedded in tomato plant tissues. Issue 3 (2nd February 2015) - Rozenberg, Tamir; Shaltiel‐Harpaz, Liora; Coll, Moshe
Abstract Nesidiocoris tenuis (Heteroptera: Miridae) is a predator of some major pests of Solanaceae crops, yet it is scarcely used in biological control because it also feeds on plants and may damage crops. The study of N. tenuis biology may promote the ability to use it as a biological control agent. Because N. tenuis, like some other insect taxa, oviposits into plant tissues, its eggs are hard to detect. This limits our ability to study N. tenuis – plant interactions. We therefore looked for a staining method for plant‐embedded eggs, which will allow their detection within tomato plants, a common host of N. tenuis. We first used lactophenol solution with acid fuchsin to stain eggs inside tomato foliage. Because of the high toxicity of lactophenol, we later substituted lactophenol with a lactoglycerol solution, which was found to be similarly efficient. Five minutes immersion in the staining solution at 80°C followed by a two‐minute soak in hot water made the eggs stain deep red, while the foliage became transparent and was stained weak red. Eggs within leaves were easily visible under 10–30× magnification with sub‐stage lighting; top‐lighting was needed for the detection of eggs embedded in less‐transparent tissues such as stems. This rapid staining method improves the ability to study some important biological aspects of N. tenuis, such as its fecundity. Also, the elimination of phenol made the method cheaper and safer to use. Finally, this method may be adapted for other arthropod–plant systems.